Che cos’è l’inclusione scolastica? Riflessioni e proposte operative - Franceschini, Giuliano (Studi sulla Formazione/Open Journal of Education, 2023)
Within a few years the canon of skills, which reigned unchallenged for the first twenty years of the new century, was quickly replaced by that of inclusion, both nationally and internationally. In this contribution we do not want to dwell on the historical-cultural contingencies that have led to this reversal, we prefer to dwell on the idea of inclusive school and how it can actually be achieved.